O ensino da escrita no último ano da Educação Infantil: práticas convertidas ao traçado das letras excludentes à noção de símbolo - Garla, Juliane de Cássia [UNESP] (Universidade Estadual Paulista (Unesp), 2016)
The theme of the writing learning in childhood education has conquered space in academic works, which occupy in analyze and understand how this process in contexts of meaning and not more before the mechanics of learning letters. Thus, in this work, it constitutes general objective to investigate whether and how the practice of teaching of oral and written expression in the last year of child education promotes the development of the symbol (sign) in children, so necessary to the learning of writing from inside to outside. The questions that served as the North for the study were the following: the teaching of writing, in the last year of child education, is organized to promote the development of the symbol (sign) in children? Which and how the ratings graphics made by children demarcate the stage of development of their writing? For its implementation, a bibliographic research was performed, using as a theoretical support for the prospect of Psychology socio-historical, especially authors as Vygotsky (1984), Luria (2001), Oliveira (1995) and Mello (2005). In addition to this was performed the empirical research of qualitative approach, according to his purpose. The data were collected by six instruments: systematic observation and direct in the classroom; audio-recording; records in a field diary, annual teaching plan of the school; lesson plan weekly and material produced by children, result of write activities. By means of the analysis of these data, we note that the writing has been worked from outside to inside, as an imposition, practice that opposes the theory of Vygotsky, already that the writing has been tackled in a way mechanical, in contexts not significant, with focused practices to the trace of the letters and copy of words, exclusive to the notion of symbol. This result points to the emergence of changes in education of writing in childhood education, without which becomes inglorious the search for a pedagogy of writing aware and...

O tema aprendizagem da escrita na Educação Infantil tem conquistado espaço em trabalhos acadêmicos, os quais se ocupam em analisar e compreender como se dá esse processo em contextos de significado e não mais diante da aprendizagem mecânica das letras. Assim, neste trabalho, constitui-se como objetivo geral investigar se e como a prática de ensino de expressão oral e escrita no último ano da Educação Infantil promove o desenvolvimento do símbolo (signo) na criança, tão necessário à aprendizagem da escrita de dentro para fora. As perguntas que serviram de norte para a pesquisa foram as seguintes: O ensino da escrita, no último ano da Educação Infantil, está organizado para promover o desenvolvimento do símbolo (signo) na criança? Como e quais as notações gráficas feitas pelas crianças demarcam o estágio de desenvolvimento da sua escrita? Para sua realização, foi feita uma pesquisa bibliográfica, utilizando como suporte teórico a perspectiva da Psicologia sócio-histórica, especialmente autores como Vygotsky (1984), Luria (2001), Oliveira (1995) e Mello (2005). Além desta foi feita a pesquisa empírica, de abordagem qualitativa, segundo seu objetivo. Os dados foram coletados por seis instrumentos: observação sistemática e direta em sala de aula; gravação em áudio; registros em diário de campo, plano de ensino anual da escola; plano de aula semanal e material produzido pelas crianças, resultado das atividades de escrita. Por meio da análise desses dados, constatamos que a escrita tem sido trabalhada de fora para dentro, como uma imposição, prática que se opõe a teoria de Vygotsky, já que a escrita tem sido abordada de maneira mecânica, em contextos não significativos, com práticas voltadas ao traçado das letras e cópia de palavras, excludentes à noção de símbolo. Esse resultado aponta para a emergência de mudanças no ensino da escrita na Educação Infantil, sem as quais se torna inglória a...
Keywords: Escrita na literatura; Aprendizagem perceptiva; Simbolismo na literatura; Educação de crianças; Psicologia social - Pesquisa; Caligrafia (Ensino); Writing in literature